2019
DOI: 10.1186/s12957-019-1656-y
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the comparison of the incidence of seeding metastasis between endoscopic biliary drainage and percutaneous transhepatic biliary drainage for resectable malignant biliary obstruction

Abstract: Background and aim Endoscopic biliary drainage (EBD) and percutaneous biliary drainage (PTBD) are the two main strategies of preoperative biliary drainage (PBD) for resectable malignant biliary obstruction (MBO) worldwide, but which is better remains unclear. Seeding metastasis (SM) has been reported repeatedly in the recent decade, although it is rarely taken into consideration in the choice of PBD. Hence, a systematic review was badly warranted to evaluate the incidence of SM between PTBD and EB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 31 publications
2
40
0
Order By: Relevance
“…In addition, as a preoperative drainage, especially in the case of resectable HCCA, seeding metastasis by PTBD is a serious problem. A systematic review showed that the incidence of seeding metastasis was significantly higher in the PTBD group (10.5% in ERBD group vs 22.0% in PTBD group, OR = 0.35, 95% CI: 0.23–0.53) …”
Section: Endoscopic Versus Percutaneous Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as a preoperative drainage, especially in the case of resectable HCCA, seeding metastasis by PTBD is a serious problem. A systematic review showed that the incidence of seeding metastasis was significantly higher in the PTBD group (10.5% in ERBD group vs 22.0% in PTBD group, OR = 0.35, 95% CI: 0.23–0.53) …”
Section: Endoscopic Versus Percutaneous Approachmentioning
confidence: 99%
“…A systematic review showed that the incidence of seeding metastasis was significantly higher in the PTBD group (10.5% in ERBD group vs 22.0% in PTBD group, OR = 0.35, 95% CI: 0.23-0.53). 19 From a technical point of view, PTBD is difficult if the intrahepatic bile duct (IHD) is not fully dilated, or if there are multiple liver metastases, ascites, or blood clots. Multiple percutaneous punctures are also needed for multiple stents, and the placement of metal stents usually requires two intervening steps.…”
Section: Endoscopic Versus Percutaneous Approachmentioning
confidence: 99%
“…It has been reported that PBD can cause complications such as biliary hemorrhage, acute cholangitis, and acute pancreatitis, with an incidence of 8%. In addition, PBD can also cause bacterial contamination of bile, and therefore increases the probability of infection after an operation, and even metastasis of tumors [5][6][7]. PTBD belongs to invasive drainage, which can be placed with multiple drainage tubes to relieve jaundice.…”
Section: Introductionmentioning
confidence: 99%
“…The most corroborated risk is transhepatic drainage for malignant biliary obstructions [14][15][16]. The prevalence of catheter tract seeding is somewhat disputed, with two reviews displaying rates ranging from as low as 6% to as high as 22% [17,18]. In addition, soft tissue spread is not unique to GI malignancies; for example, an intracranial glioma has been reported to disperse into the peritoneum via a ventricular shunt [19].…”
Section: Discussionmentioning
confidence: 99%